An interactive environment for a mobile robot using skin detection - Wong, Hwee Ling (2003)
This paper presents an interactive computer environment to be implemented on a mobile robot for human-robot interface (HRI) by incorporating skin detection technique. Human face detection yielded by visual sensor is the core towards an interaction between human and robots. Hence, efficient skin detection can serve as the basis towards producing fast face feature extraction for robotics application. The proposed skin detection method is based on color space analysis. The goal is to demonstrate that a common pattern exists among human skin color. In order to support the human-robot interaction application, a hardware and software structure is proposed for the HRI.